2021
DOI: 10.7160/eriesj.2021.140304
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Accountability for Teacher Occupational Professionalism: The Effect of Accountability on Occupational Awareness with the Mediating Roles of Contribution to Organization, Emotional Labor and Personal Development

Abstract: Accountability enables teachers to exhibit professional behaviors in school processes. However, the contribution of accountability to teacher occupational professionalism depends on the effective structuring of accountability mechanisms. It is necessary to examine how the connection between teacher occupational professionalism and accountability can be effectively established in line with different conceptual models. Therefore, this study investigated the relationship between teacher accountability and occupat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Despite the differences between the schools' cultures and dynamics of transformation, schools have become more performance-oriented after external evaluation. Lack of accountability and control is a factor that leads to low-performing schools (Küçükbere & Balkar, 2021). However, the self-evaluation process post-external evaluation still reveals weaknesses regarding (i) the evaluation of goals fulfilment of guiding documents, (ii) the evaluation of school services, (iii) monitoring of discipline, (iv) participation by the community, (iv) the use, diffusion, and reflection of external and internal evaluation data, (v) innovation oriented-self-evaluation practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the differences between the schools' cultures and dynamics of transformation, schools have become more performance-oriented after external evaluation. Lack of accountability and control is a factor that leads to low-performing schools (Küçükbere & Balkar, 2021). However, the self-evaluation process post-external evaluation still reveals weaknesses regarding (i) the evaluation of goals fulfilment of guiding documents, (ii) the evaluation of school services, (iii) monitoring of discipline, (iv) participation by the community, (iv) the use, diffusion, and reflection of external and internal evaluation data, (v) innovation oriented-self-evaluation practices.…”
Section: Discussionmentioning
confidence: 99%
“…Combining control-and improvement-oriented evaluation systems may promote school development and enhance education quality (Hanberger et al, 2016). The importance of a supportive school evaluation and innovation is highlighted by the European Inspectorate (Donaldson, 2013;Simeonova et al, 2020) and by scholars (Brown et al, 2018;Hanberger et al, 2016;Küçükbere & Balkar, 2021;Kurum & Cinkir, 2019;McNamara & O'Hara, 2008;Monarca & Fernández-González, 2016). Pursuing a culture of permanent improvement is about knowing which factors induce teachers' innovative behaviour to support the school's transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of teachers is one of the most important factors affecting the education system. The teacher accountability movement is one of the most controversial and important topics in modern educational reform [16]. Too much previous research has shown how teachers can improve their teaching methods, how to train teachers, etc.…”
Section: The Impact Of Teacher Accountability On Educational Equity I...mentioning
confidence: 99%
“…Researchers use different research options to improve educational equity or force educators and policymakers to improve traditional academic-quality schools for underserved student populations [15]. Hodgetts (2010) pointed out that the current education system emphasizes teachers' responsibility by focusing on performance [16]. But the impact of teacher job satisfaction on educational equity has not been discussed much throughout the teacher accountability system.…”
Section: The Impact Of Teacher Accountability On Educational Equity I...mentioning
confidence: 99%
“…The lecturers' accountability, professional identity and subject matter, pedagogical, and didactic expertise distinctness supported students' narrative writing practices shall appropriately develop academic skills (Geletu & Mihirete, 2022) by accommodating a constructivist assessment model (Sumekto & Setyawati, 2018;. Hence, effective lecturers accomplish their professional development and occupational professionalism requirements to fulfill the systematic and planned manners (Küçükbere & Balkar, 2021).…”
Section: Introductionmentioning
confidence: 99%